Parents' Perceptions of a Serious Game for Educating Families on Prescription Opioid Safety: Qualitative Pilot Study of MedSMARxT: Adventures in PharmaCity - Olufunmilola Abraham; Grace Ann Nixon; Laura Louise Seitz (JMIR Publications, 2023)
BackgroundOpioid misuse is a pervasive, worsening problem that affects the health of people throughout the United States, including adolescents. There are few adolescent-focused interventions designed to educate them about opioid medication safety. The MedSMARxT: Adventures in PharmaCity, is a serious educational video game that teaches parents and their youths about safe opioid practices. ObjectiveThis study aimed to elucidate parent's perceptions of MedSMARxT: Adventures in PharmaCity and its potential use by parents and their adolescents. MethodsParents of adolescents aged 12 to 18 years who live in the United States were recruited from April to October 2021 via Qualtrics research panels, social media, email listserves, and snowball sampling. The study participants played MedSMARxT: Adventures in PharmaCity for 30 minutes and then participated in a 30-minute postgame interview via WebEx (Cisco). Questions were developed and piloted to examine adults' perceptions of the game. Participants were asked three sets of open-ended questions: (1) questions about the game and elements of the game, (2) what they learned from the game, and (3) questions about their experience with games. Audio recordings were transcribed verbatim. Interview transcripts were coded using content and thematic analysis by study team members to identify major themes and subthemes from the data. ResultsParent participants (N=67) played MedSMARxT: Adventures in PharmaCity and completed a postgame interview. Analysis extrapolated four primary themes from the data: (1) participant gaming experience, (2) perception of game features, (3) educational purpose of the game, and (4) future use of the game. Most participants (n=56, 84%), had at least some experience with video games. More than half of the participants (n=35, 52%) participants, had positive reactions to the game characters and scenes depicted in MedSMARxT: Adventures in PharmaCity and stated they were realistic for adolescents. Most participants (n=39, 58%), would recommend the game to others. Significant difficulties with gameplay navigation were reported by 38 (57%) participants, as well as a slow game pace. All participants were able to accurately identify the overarching goal of the game: opioid or medication safety. The game reinforced existing knowledge for participants, though many (n=15, 22%), reported a new awareness of the need to store opioid medications in a locked area and the availability of medication disposal drop boxes at pharmacies. Participants stated that they would recommend the game for future use by families and youths in various health care and non-health care settings. ConclusionsThe use of a tailored serious game is a novel, engaging tool to educate adolescents on opioid safety. MedSMARxT: Adventures in PharmaCity can be used as a tool for parents and adolescents to facilitate meaningful dialogue about safe and appropriate opioid use.